Learning Qlik Sense : the official guide get to grips with the vision of Qlik Sense for next generation business intelligence and data discovery /: the official guide get to grips with the vision of Qlik Sense for next generation business intelligence and data discovery. (2015) - Ilacqua, Christopher; Cronström, Henric; Richardson, James
No abstract available